2003
DOI: 10.1002/elps.200305381
|View full text |Cite
|
Sign up to set email alerts
|

Size‐exclusion capillary electrochromatographic separation of polysaccharides using polymeric stationary phases

Abstract: We report the successful size-based separations of large, neutral polysaccharides using capillary electrochromatography (CEC). As the polysaccharides possessed little chromophore for photometric detection, two separate approaches were taken. In the first approach, indirect detection was combined with size-exclusion chromatography using a sulfonated polystyrene/divinylbenzene stationary phase. The separations were performed using a 300 Å pore size stationary phase under aqueous conditions. Nonsize based interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 77 publications
0
3
1
Order By: Relevance
“…1) demonstrate that a locally flat velocity profile for electrokinetic flow through the interparticle pore space of packed beds which are employed for EC separations in capillary and chip format does not exist, even in the thin-EDLlimit and with uniform surface properties throughout the packing. These results contradict relatively early anticipation [59][60][61] which still finds widespread acceptance [62][63][64][65][66][67][68][69].…”
Section: Pore-scale Eof In Packed Beds Of Nonporous Particlescontrasting
confidence: 66%
“…1) demonstrate that a locally flat velocity profile for electrokinetic flow through the interparticle pore space of packed beds which are employed for EC separations in capillary and chip format does not exist, even in the thin-EDLlimit and with uniform surface properties throughout the packing. These results contradict relatively early anticipation [59][60][61] which still finds widespread acceptance [62][63][64][65][66][67][68][69].…”
Section: Pore-scale Eof In Packed Beds Of Nonporous Particlescontrasting
confidence: 66%
“…Using this calibration, molecular weights of fractions J-I, J-II, J-III, J-IV, and J-V were estimated to be 680, 200, 100, 60 and 30 kDa, respectively. Furthermore, evaluation of the detector response as a function of polysaccharide concentration [28] indicated that the response was linear over the range of 0.25-2 mg/ml. Based on these results it appears that self-aggregation of the polysaccharides, which could falsely lead to high molecular weight determinations, did not occur with our assay.…”
Section: Preparation and Partial Characterization Of Juniper Polysaccmentioning
confidence: 98%
“…Electrophoresis without supporting gels has been exploited to develop separation methods, where the gels are used as functional elements of electrokinetic separation methods [10]. Examples are sol-gel based electrochromatography [11,12] and CIEF [13]. Additives of uncrosslinked polymers can be used to improve the separation of probe constituents in microchannels.…”
Section: Introductionmentioning
confidence: 99%